Beyond databases, architectures and structures : advanced technologies for data mining and knowledge discovery : 12th International Conference, BDAS 2016, Ustroń, Poland, May 31-June 3, 2016, Proceedings /: advanced technologies for data mining and knowledge discovery : 12th International Conference, BDAS 2016, Ustroń, Poland, May 31-June 3, 2016, Proceedings. (2016) - Unknown
No abstract available